1979
DOI: 10.1002/ijc.2910230512
|View full text |Cite
|
Sign up to set email alerts
|

Immune suppression in BALB/c mice bearing the plasmacytoma TEPC‐183: Evidence for normal lymphocyte but defective macrophage function

Abstract: This paper analyses impairment of the primary immune response of mice bearing the plasmacytoma TEPC-183. Healthy animals and mice bearing the reported non-immunosuppressive tumour MOPC-104E were used as controls. The defect was shown to affect both primary IgG and IgM responses to chicken cells (CRBC) and to be related to tumour size. However, the primary immune depression could be overcome either by increasing the antigen dose or by using Freund's complete adjuvant together with antigen. Secondary responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other studies have demonstrated a reversible defect in the natural killer cells of patients with MM (Dhodapkar et al , 2003). Early murine studies suggested that the poor immune response was due to a defect in antigen‐presenting cells (Joshua et al , 1979) and more recently a defect in the DC of patients with MM has been defined by our group and others (Brown et al , 2001; Ratta et al , 2002). Thus, the poor response to idiotype vaccination and other active immunotherapy strategies in these patients (Ruffini et al , 2002) should have been expected.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated a reversible defect in the natural killer cells of patients with MM (Dhodapkar et al , 2003). Early murine studies suggested that the poor immune response was due to a defect in antigen‐presenting cells (Joshua et al , 1979) and more recently a defect in the DC of patients with MM has been defined by our group and others (Brown et al , 2001; Ratta et al , 2002). Thus, the poor response to idiotype vaccination and other active immunotherapy strategies in these patients (Ruffini et al , 2002) should have been expected.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with myeloma respond poorly to immunization by viral and bacterial antigens, 7 and murine studies have suggested that this defect is associated with APCs rather than with T cells. 8 It is, therefore, not surprising that idiotype vaccination trials have had little success. Clearly, more careful consideration of the biology of host-tumor interactions, including an understanding of the induction of T-cell tolerance by tumor antigens and a characterization of the dysfunction of APCs in patients with myeloma, is required before more effective immunotherapy schedules can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…7 Murine studies have suggested that this defect is associated with antigen presenting cells (APCs). 8 There have been reports that the DCs of patients with myeloma are functionally normal 9,10 ; however, the criteria used to define DCs in these latter studies included monocytes-macrophages and even B cells. Preliminary reports of immunotherapy trials in patients with myeloma have demonstrated only minor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been postulated from experimental work in human and animal B-cell neoplasia to explain the mechanism or mechanisms of secondary hypogammaglobulinaemia. These include: hypercatabolism of antibody (Lippincott et al, 1960;Solomon et al, 1963); increased action of suppressor cells (Broder er al., 1975;Krakauer et al, 1977;Kolb et al, 1977); B-cell inactivation by tumour RNA (Heller et al, 1973) and defective antigen processing (Joshua et al, 1979). This variety of postulated mechanisms may in part reflect differences in the types of B-cell tumour studied.…”
mentioning
confidence: 99%